2013
DOI: 10.1136/jech-2013-203057
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in all-cause mortality in the Czech Republic, Russia, Poland and Lithuania in the 2000s: findings from the HAPIEE Study

Abstract: BackgroundRelatively large socioeconomic inequalities in health and mortality have been observed in Central and Eastern Europe (CEE) and the former Soviet Union (FSU). Yet comparative data are sparse and virtually all studies include only education. The aim of this study is to quantify and compare socioeconomic inequalities in all-cause mortality during the 2000s in urban population samples from four CEE/FSU countries, by three different measures of socioeconomic position (SEP) (education, difficulty buying fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
35
2
6

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 33 publications
3
35
2
6
Order By: Relevance
“…The historic dynamics of the total death rates demonstrates the certain role of the socio-economic disasters for both total and CV mortality, for instance in 90s after the dissolution of the Soviet Union and a default of 1998 (25,28,30), but most probably it makes a sense exceptionally in case of the larger dramatic economic events with the pronounced impoverishment of the population and degradation of the social life with significant changes in a lifestyle which was previously confirmed in both MONICA and HAPIEE studies that observed different populations in the Eastern Europe (1,29,30). The Russian mortality trend documents the dramatic increase of death rates after 1988 at the phase of the Soviet degradation (with a fold GDP decline of −0.36) and the further drop after 2002 with the lowest GDP (PPP) per capita of 8,539.00 U.S. dollars in 1998 growing up to actual $23,292.91 in 2016 amid broad reforms of both the Russian economics and public health system.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The historic dynamics of the total death rates demonstrates the certain role of the socio-economic disasters for both total and CV mortality, for instance in 90s after the dissolution of the Soviet Union and a default of 1998 (25,28,30), but most probably it makes a sense exceptionally in case of the larger dramatic economic events with the pronounced impoverishment of the population and degradation of the social life with significant changes in a lifestyle which was previously confirmed in both MONICA and HAPIEE studies that observed different populations in the Eastern Europe (1,29,30). The Russian mortality trend documents the dramatic increase of death rates after 1988 at the phase of the Soviet degradation (with a fold GDP decline of −0.36) and the further drop after 2002 with the lowest GDP (PPP) per capita of 8,539.00 U.S. dollars in 1998 growing up to actual $23,292.91 in 2016 amid broad reforms of both the Russian economics and public health system.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…The smoking (17.3% of screened with a 2,786 cig a year; 63.2% of male and 9.1% of female; 70.6% in the trial; a contribution to mortality is about 29%), excessive alcohol consumption (1.8% of screened with a 11.6 L per year mostly of beer and vodka; 50.6% in the trial; about 70% consumed strong alcoholic beverages; responsible for 25.6% of CV deaths in male and 15.4% in female), unhealthy diet with insufficient consumption of fruits, vegetables, sea food, unsaturated fat, and proteins (mean 12% of the daily consumption) with abundance of carbohydrates/ sugar (up to 57% of diet), saturated and trans fats (up to 29-40% of the energy) including palm oil, butterfat, mayonnaise, and junk processed red meat), psychosocial factors (75% of Russians are not adapted to new living conditions, 20%-stress, 11.7%-anxiety, and 9.6%-depression) and physical inactivity (19.6% of screened; at least 73.9% of men and 74.8% of women) remain the major modifiable risk factors. They, in turn, affect (see Figure 3) (5,14,15,(17)(18)(19)(20)(21)(22)(25)(26)(27)(28)(29)(30) such risk factors as dyslipidemia (86.7% in the trial), obesity (16.7% of screened; mean BMI in the trial was 28.4), and hypertension (about 40.8% suffered; 86.1% in the trial), which is relevant to findings of the EUROASPIRE IV trial (31,32) in the European population, and screening studies of the Russian Cardiovasc Diagn Ther 2017;7(1):60-84 cdt.amegroups.com 1980 1982 1984 1986 1988 1990 1992 1994 1996 1998 Total mortality per 1,000, 2012…”
Section: Cardiovascular Mortality and Major National Risk Factorsmentioning
confidence: 99%
“…In this issue, Vandenheede et al 1 publish new evidence for the presence of socioeconomic inequalities in all-cause mortality in three countries from Central/Eastern Europe (CEE) and in Russia. Although each of the four countries has faced different transitions in their population health after the fall of the Iron Curtain, relative differences in mortality are found in each of the four countries.…”
mentioning
confidence: 99%
“…So, despite the fact that lower SES groups in all countries are engaging more in unhealthy behaviours than higher SES groups, the extent to which lower SES people are adopting these behaviours seems to be heavily determined by the societal and macroeconomic context. As for the Eastern European countries, it is highly likely that the societal changes following the collapse of the Soviet Union played a major role 1 10. The main strength of the study by Mackenbach et al 1 lies in its possibility to provide clear clues on proximal and distal determinants of mortality inequalities and, hence, opening up opportunities for further (explanatory) research.…”
mentioning
confidence: 99%